FEATURES OF THE BILIARY TRACT DYSFUNCTIONAL DISORDERS DURING NON-REMOVABLE EQUIPMENT TREATMENT IN CHILDREN WITH DENTOALVEOLAR ANOMALIES - Тамара Анатольевна Сиротченко; Юрий Анатольевич Калиниченко; Анна Александровна Бобрышева (The Publishing House Medicine and Enlightenment, 2017)
Children biliary dysfunction occupied a leading place in the structure of gastroenterological diseases. During the long orthodontic treatment the dental anomalies supported dysfunction of biliary system and contributed to its progression. It was necessary to confirm the relationship of oral disease and biliary system in children with dentoalveolar anomalies and proved the possibility of mutual aggravation. The study involved 65 schoolchildren aged 12-16 years with biliary dysfunction: 35 people have been without dental anomalies (study group) and 30 schoolchildren (control group) with biliary dysfunction and dental anomalies. It is proved that the use of orthodontic appliances have an adverse effect on biliary tract function. A normal function condition of biliary system is necessary for normalization of bile flow during orthodontic equipment treatment in children.